2014
DOI: 10.1007/s00417-014-2697-0
|View full text |Cite
|
Sign up to set email alerts
|

Early axonal damage detection by ganglion cell complex analysis with optical coherence tomography in nonarteritic anterior ischaemic optic neuropathy

Abstract: GCC thickness measurement by OCT is capable of detecting early axonal damage in NAION eyes in the acute phase that cannot be detected by RNFL. GCC defects are significantly correlated with visual field globally and the defect location.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 26 publications
3
30
1
1
Order By: Relevance
“…These results differed from those of previous studies, which reported that late pRNFL and mGCIPL thickness showed a regional correlation with late VF defects [7,14]. Larrea et al, however, reported that regional correlations between mGCIPL thickness in the chronic stage of NAION and the final VF defect were not significant [12]. We agree with their opinion that GCL damage becomes more severe and diffuse with time, and that increasing damage to internal plexus layer cells, such as glial cells, is possible.…”
Section: Discussioncontrasting
confidence: 98%
See 3 more Smart Citations
“…These results differed from those of previous studies, which reported that late pRNFL and mGCIPL thickness showed a regional correlation with late VF defects [7,14]. Larrea et al, however, reported that regional correlations between mGCIPL thickness in the chronic stage of NAION and the final VF defect were not significant [12]. We agree with their opinion that GCL damage becomes more severe and diffuse with time, and that increasing damage to internal plexus layer cells, such as glial cells, is possible.…”
Section: Discussioncontrasting
confidence: 98%
“…These studies showed that loss of the macular ganglion cell complex in the late phase correlated well with VF loss in both magnitude and location. Only one study has investigated mGCIPL loss in the early phase (6 weeks or less after the acute episode) of NAION [12]. This study reported that 54.5 % of the patients examined showed pRNFL thinning and 77.3 % showed mGCIPL thinning in the early phase.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using Fourier-domain OCT, Aggarwal et al showed high correlation of the macular GCC thickness with visual fi eld losses in both magnitude and location in patients with NAION, with hemispheric GCC loss correlating with altitudinal visual fi eld loss [ 29 ]. Larrea et al showed a signifi cant correlation between GCC averages at the onset of NAION and visual fi eld losses in both acute and chronic stages, suggesting that GCC thickness in the acute stage may be a determining factor to predict fi nal visual fi eld defects, with good correlation between location of damage in the GCC in the macular region and location of the scotoma [ 31 ].…”
Section: Papilledemamentioning
confidence: 99%